2020
DOI: 10.1088/1742-6596/1529/4/042075
|View full text |Cite
|
Sign up to set email alerts
|

Brain Controlled Wheelchair: A Smart Prototype

Abstract: EEG has been largely used in both clinical and research applications. Brain computer interface (BCI) system is one of the major EEG research applications which can provide a new way of communications for special users who cannot communicate via normal pathways. This paper focuses on the development of the brain controlled wheelchair which incorporates two additional control interfaces including joystick and a remote control through an android phone. All three controls are integrated in such a way that it allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Figures 15(b The test setup of the first Test subject-1 is shown in Figure . 15(a). The subject is wearing the headwear making sure that the frontal EEG electrode is placed precisely at FP1 [17,27]. Before electrode placement, the skin at FP1 is cleaned with cotton to reduce skin impedance.…”
Section: Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 15(b The test setup of the first Test subject-1 is shown in Figure . 15(a). The subject is wearing the headwear making sure that the frontal EEG electrode is placed precisely at FP1 [17,27]. Before electrode placement, the skin at FP1 is cleaned with cotton to reduce skin impedance.…”
Section: Test Resultsmentioning
confidence: 99%
“…The TGAM module is powered by a battery pack that supplies a cumulative voltage of 4.5V. A single channel non-invasive silver EEG electrode placed at the pre-frontal lobe (FP1) [17,27,28] extracts electrical signals from the scalp of the subject. This particular FP1 placement is used because FP1 and FP2 placements show the greatest deflection of potential in a time-domain EEG waveform [29].…”
Section: Headwearmentioning
confidence: 99%
“…Different pre-processing techniques including DC offset correction (i.e., high pass filter at 0.1 Hz), electrical interference removal (notch filter at 60 Hz) and bandpass filtration has been applied to clean EEG data. The raw EEG data was bandpass filtered between 7 Hz and 30 Hz to eliminate all the frequency components other than mu and beta as the studies [7][8][9] revealed the occurrence of MI patterns in the stated frequency range.…”
Section: Methodsmentioning
confidence: 99%
“…A high-pass filter was applied at 0.1 Hz for the purpose of DC offset correction, while a notch filter was used at 60 Hz to eliminate the electrical interference. The raw signal was bandpass filtered between 7 and 32 Hz to exclude all of the frequency components other than mu and beta, as the studies [ 43 , 44 , 45 ] revealed the occurrence of MI patterns in the stated frequency range. However, the artifacts were removed using the EEGLAB-based artifact removal algorithm called artifact subspace reconstruction (ASR).…”
Section: Methodsmentioning
confidence: 99%